REFORMING OF HIGHER EDUCATION IN THE UK: VALUE AND NORMATIVE DIMENSIONS - Elizaveta V. Zolotareva (Высшее образование в России)
Abstract. Evolution strategy for reforming higher education in the UK during the transition from binary to a unitary system is considered in the context of existing alternative approaches to the choice of strategic priorities, forms and methods of educational process regulation, set out in the policy reports of Lord Robbins (1963), Lord Dearing (1997) and Lord Browne (2010).The contradictory nature of neoliberal policy reforms in the last 25 years is seen as a reflection of tensions between the socioBcultural and economic functions of education, the underlying conflict between technocratic, social and humanistic approaches to solving the problem of higher education to adapt to the new technological and social reality of the twentyBfirst century. The conflict of interpretations by main political actors of such principles as social justice, freedom of choice, responsibility and efficiency is projected on their choice of strategy of forming «new» partnerships between educational subjects – universities, students, business and the state. Heuristic possibilities of using the method of critical discourseBanalysis to improve the regulatory framework in a crisis situation, and reducing risk in making innovative solutions, especially for young people, is considered by the example of the analysis of I. Fairclouch and N. Fairclouch parliamentary debate in 2010 to raise tuition fees in universities.